Development of a finite element analysis program for truss analysis - Zamzul Khairi Bin Zulkifli (2023)
The purpose of this final year project is to develop an engineering software that is user-friendly, cost-efficient, reliable, and can provide precise results. The program was written using Microsoft Visual basic 6.0. It can be used in designing and analysis purposes. The software module developed is called 'TRUSSnalysis Version 1.1'. This software is for designing and analyzing 2 dimensional trusses using the finite element method. However, the program does not cover trusses with temperature variation and multipoint constraints.